P025 Identification and validation of predictors for tofacitinib through supervised and unbiased approaches in Inflammatory Bowel Disease. (27th May 2021) - Liu, B; Spalinger, M; Perez, L G; Machicote, A; Gagliani, N; Scharl, M; Huber, S
Abstract: Background: Inflammatory Bowel Disease (IBD) is characterized by an overwhelming gut inflammation, where CD4 + effector T cells are main mediators of the inflammatory response. Tofacitinib, a small molecular drug recently used in IBD patients, blocks the JAK/STAT signaling pathway necessary for CD4 + effector T-cell activation. However, clinical data show that a percentage of patients do not respond to the treatment. Our main goal is to identify biomarkers predicting the response of patients to tofacitinib. Methods: Tofacitinib efficacy was studied in vivo in wild type (WT) and T-cell-specific PTPN2 deficient mice (CD4-Cre;Ptpn2 floxed) in which the JAK/STAT signaling pathway is over activated. WT and PTPN2 deficient mice were gavaged with tofacitinib (50mg/kg, twice daily) or vehicle. Acute DSS-colitis was induced. Colitis development was evaluated by weight loss, colonoscopy and histology. CD4 + T cells were isolated from the colon and analyzed by flow cytometry. To study the effect of tofacitinib on T-cell differentiation, we isolated naïve T cells from mouse spleen and polarized them in vitro to different T-cell subsets with or without tofacitinib. CD4 + T cells differentiation and cytokine production were analyzed by flow cytometry. To evaluate the influence of tofacitinib on human CD4 + T cells, human peripheral blood mononuclear cells (PBMCs) from healthy donors and IBD patients were stimulated in presence of tofacitinib, and analyzed by flow cytometry. Results: While no protective effect was found after tofacitinib treatment in WT mice, PTPN2 deficient mice were protected from colitis based on less weight loss, lower endoscopic and histological scores. The expression of pro-inflammatory cytokines such as IL-17 and IFN-γ by colonic CD4 + T cells was also decreased by tofacitinib. Consistent with the in vivo observations, in vitro experiments revealed a strong impact of tofacitinib on CD4 + T-cells cytokine production. In PBMCs from IBD patients, IFN-γ and TNF-α expression was strongly impacted. In contrast, in healthy donors, IL-10 was the most impacted cytokine. Finally, tofacitinib decreased the in vitro differentiation of Th1, Th2, Th17, Th22, Treg and Tr1. Conclusion: In the T-cell-specific PTPN2 deficient mice, tofacitinib exerts a protective effect after DSS-induced colitis. In line with the in vivo findings, in vitro experiments show that tofacitinib has a strong impact on pro-inflammatory cytokine production, especially in the IBD patients. Taken together, these data suggest that tofacitinib might be suitable primarily for IBD patients where the JAK/STAT signaling pathway is over activated.